Chiari Malformation Type I: A Neuropsychological Case Study. Issue 6 (1st June 2014) - Klein, Robert; Hopewell, C. Alan; Oien, Michael
ABSTRACT: Chiari Malformation type I (CM-I) is a congenital anomaly that occurs when the cerebellar tonsils protrude through the foramen magnum. Individuals with this condition are typically asymptomatic and the identification of the malformation is usually an incidental finding during the course of treating another disorder. This case study explores the neuropsychological sequelae of two unique cases of CM-I in combat veterans. Neuropsychological evaluation revealed that both patients demonstrated preserved general cognitive functioning but had varying patterns of performance on measures of visuospatial, executive functioning, and processing speed. In terms of affective functioning, both endorsed significant depressive symptomatology, but had varying patterns of severity on other estimates of psychiatric symptomatology. Overall, results suggest that there is not one pattern of cognitive and affective functioning associated with CM-I and that environmental and psychological rather than neurological factors should be considered when evaluating cognitive and affective functioning. These cases also highlight the need for neuropsychological evaluation in CM-I in terms of providing guidance for psychoeducation and psychotherapy.